THE IMPACT OF PRICE CHANGES ON INPUT DEMAND AND OUTPUT SUPPLY IN THE UPLAND RICE FARMING OF BOYOLALI DISTRICT, CENTRAL JAVA, INDONESIA - Dewi Sahara*, Komalawati, Forita Dyah Arianti, Atman, Idaryani, Jefny B. Markus Rawung, Muhammad A. Mustaha, A. Yulyani Fadwiwati, Lis. M. Yapanto, Rita Indrasti, Siti Sehat Tan, Rubiyo (Chelonian Research Foundation, 2023)
The change in rice and production input prices will influence farmer decision for rice production. The study aimed to find an influence of production inputs and upland rice prices on rice supply and input production demands. The study was conducted at Kebonbimo Villages, Winong Subdistrict, and Sukorame Villages, Musuk Subdistrict, Boyolali District from February to April 2018. The study used a method survey. Data collected in the study were household characteristics, quantity, and prices of production inputs, quantity, and output prices. Data were analyzed by Seemingly Unrelated Regression (SUR). Results of the study indicated that change of rice prices was elastics to upland rice supply and production input demand, while production input prices change were inelastic to upland rice supply, except for change of labor’s wage. The elasticity value of production input demand to own price was -0.36 to -2.63, indicating that the high change of production input prices was led to reducing production input demands. The change of planting area and family members caused a direct change to upland rice supply dan production input demands. Therefore, increasing the upland rice supply can be done by increasing price and expanding the upland rice planting area. Keywords: demand, elasticity, upland rice, supply, price change